2013
DOI: 10.1037/a0030960
|View full text |Cite
|
Sign up to set email alerts
|

Theory and research on gender are always precarious.

Abstract: Scientific and social values are inevitably embedded in any scholarship, but theory and research on gender can be particularly precarious given the contextual and constitutive nature of gendered experiences. We consider the body of research on precarious manhood from a broader perspective on values and goals in theory and research on gender. We address not only the internal validity of research on precarious manhood, but also its potential broader social implications. We begin by summarizing a functional-conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…Within the study of men and masculinity, harassment of heterosexual boys based on sexual orientation may exacerbate a sense that one’s masculinity is tenuous and must be earned and maintained via gender conformity, consistent with the precarious manhood paradigm (Vandello et al, 2008). Numerous experimental studies have indicated that insults to men’s sense of masculinity result in increases in aggression and other forms of attempts to reassert masculinity (Addis and Schwab, 2013; Bosson et al, 2009; Kroeper et al, 2014; Weaver et al, 2010, 2013). Pursuant to AAS, muscularity has been found to be thought of as a defining characteristic of masculinity among boys and young men, and is also associated with other social markers of masculinity (e.g.…”
mentioning
confidence: 99%
“…Within the study of men and masculinity, harassment of heterosexual boys based on sexual orientation may exacerbate a sense that one’s masculinity is tenuous and must be earned and maintained via gender conformity, consistent with the precarious manhood paradigm (Vandello et al, 2008). Numerous experimental studies have indicated that insults to men’s sense of masculinity result in increases in aggression and other forms of attempts to reassert masculinity (Addis and Schwab, 2013; Bosson et al, 2009; Kroeper et al, 2014; Weaver et al, 2010, 2013). Pursuant to AAS, muscularity has been found to be thought of as a defining characteristic of masculinity among boys and young men, and is also associated with other social markers of masculinity (e.g.…”
mentioning
confidence: 99%
“…The recent review article on precarious manhood by Vandello and Bosson (2013), for instance, may gamer citations from articles on gender and social status. Thus, any citations generated by the three commentaries accompanying Vandello and Bosson's review (Addis & Schwab, 2013;Chrisler, 2013a;Heesacker & Snowden, 2013) can be seen as "bonus points. Thus, any citations generated by the three commentaries accompanying Vandello and Bosson's review (Addis & Schwab, 2013;Chrisler, 2013a;Heesacker & Snowden, 2013) can be seen as "bonus points.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, along with the focus on masculinity treat, the outcome measures in previous studies have largely been restricted to male‐typed activities and tasks. This leaves open the possibility that women also compensate for threats to their gender identity, but that they do so in other domains than men (Addis & Schwab, ). The focus on primarily masculine domains may result in hasty conclusions of women as less susceptible to gender identity threats.…”
Section: Threatened Womanhoodmentioning
confidence: 93%